Complementary Approaches to Postoperative Pain Management: A Review of Non-pharmacological Interventions - Emery Niyonkuru; Muhammad Asad Iqbal; Xu Zhang; Peng Ma (Pain and Therapy)
Abstract Postoperative pain significantly affects many surgical patients. While opioids are crucial for pain management, they come with unwanted side effects. Alternatives like nonsteroidal anti-inflammatory drugs, N-methyl-d-aspartate (NMDA) receptor antagonists, and regional anesthesia techniques such as nerve blocks are utilized, but these also have limitations. This underscores the need for complementary non-pharmacological interventions to enhance postoperative pain control and reduce opioid dependence. This study aimed to synthesize evidence on the efficacy of nondrug approaches for managing postoperative pain. The study examined the effects of non-pharmacological interventions such as preoperative patient education, mind–body modalities, and physical therapies. Findings suggest that these approaches can reduce pain intensity, decrease opioid consumption, and enhance recovery outcomes. The study also highlighted the pivotal role of healthcare professionals in implementing these strategies. However, it identified workload constraints and insufficient training as barriers to effective utilization in clinical practice. Integrating non-pharmacological interventions into multimodal pain management regimens can improve postoperative pain control and reduce reliance on opioids. Further research is crucial to definitively establish the efficacy of individual interventions and optimize their combined use in clinical practice. Additionally, enhanced training programs for nurses and initiatives to facilitate the implementation of these strategies are necessary for their successful adoption.